Kanon, klima & kreativitet: – nye stier i Pontoppidans landskaber - Eberth Timmermann, Ditte; Reeder Ryborg Jørgensen, Christina (Pontoppidaniana, 2025)
Abstract This article explores how Henrik Pontoppidan’s literature, traditionally anchored in the Danish literary canon, can be reinterpreted through the lens of contemporary ecological and educational concerns. While Pontoppidan is often taught in the context of the Modern Breakthrough with a focus on gender, class, and religion, we argue for the inclusion of a fourth element: climate. Drawing on theories of narrative learning and creativity by scholars such as Vygotsky and Piekut, we propose new didactic approaches that engage students not only analytically but also creatively and reflectively. Using examples from Lykke-Per and selected short stories, we demonstrate how Pontoppidan’s nature and landscape depictions cansupport an eco-centric worldview, fostering student engagement with climate challenges and existential questions. Furthermore, we examine how Pontoppidan’s works may offer resistance to canon rigidity and suggest paths toward a more diverse, sustainable, and imaginative literature education in upper secondary schools. By integrating narrative practices and cross-disciplinary perspectives, Danish literature can become a transformative space where students learn not only to interpret texts-but also to imagine alternative futures.